2018
DOI: 10.13189/lls.2018.060101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Task Repetition, Unguided Strategic Planning, and Pressured On-line Planning on the Accuracy of Upper-intermediate EFL Learners' Written Production

Abstract: The present study set out to explore the effects of task repetition (TR), unguided strategic planning (USP), and pressured on-line planning (POP) on the accuracy of Iranian EFL Upper-intermediate learners' written production. To achieve this, 90 EFL learners from three intact classes of an English institute were randomly assigned to three experimental groups. All participants in three groups experienced a written narrative task based on a set of six pictures as pre-test, a week prior to the 10-session treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Regarding precision and complexity, EFL learners can draw lexical and syntactic details either independently or in groups. Finding a positive effect of TR on learners' reading performance was consistent with the recommendations of Bayat (2018), who suggested that repetition enhanced the learners' usage of the language program, reading fluency and consciousness. Findings on CAF were consistent with those of previous works in preserving the reading form and meaning (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Regarding precision and complexity, EFL learners can draw lexical and syntactic details either independently or in groups. Finding a positive effect of TR on learners' reading performance was consistent with the recommendations of Bayat (2018), who suggested that repetition enhanced the learners' usage of the language program, reading fluency and consciousness. Findings on CAF were consistent with those of previous works in preserving the reading form and meaning (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…However, as repeated activities stimulate understanding and familiarity with the elements of cognitive benefits, this process overcomes the effects of restricted or limited capability. Such hypotheses are examined through activity repetition studies, and most of these studies have sought to determine if replicating similar activities influenced learner L2 learning (Bayat, 2018;Cho, 2018;Dawadi, 2019;Hopp, 2014). For example, a study conducted on college students examined whether replicating a story and meeting a task after a 10-week interval would help them perform better in most complexity, accuracy and fluency (CAF) regions (Bayat, 2018).…”
Section: Justification For the Studymentioning
confidence: 99%
See 1 more Smart Citation